The Reality of Primary School Teachers’ Practice of Professional Accreditation Standards in Light of Approaches to Teacher Professionalization from the Supervisors’ Point of View - Ali Hasoon, Amera; Kadhim Jabber, Ghasan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
The study is an attempt to identify the reality of primary school teachers’ practice of professional accreditation standards in light of approaches to teacher professionalization from the supervisors’ point of view. The study sample consisted of supervisors in the educational supervision department /Maysan Education Directorate, academic year (2024-2025). The number of supervisors was (62) male and (16) female. The researcher prepared the research tool (professional accreditation standards in light of approaches to teacher professionalization), and items for each standard follow it. Firstly, meditative practice preface: (first standard, to master the cognitive structure of the specialization) (to master the approaches and strategies of education and learning) (to be keen on the continuous professional development). Secondly, investigative approach preface: (first standard, planning), (second standard, implementation), (third standard and assessment),. Thirdly, Ethics of the education profession preface: first standard, (to be cooperative member in school and local community), second standard (the professional ethics in evaluation and examination processes), third standard (professional ethics in school activities)